Determination of Bile Acids in Piglet Bile by Solid Phase Extraction and Liquid Chromatography‐Electrospray Tandem Mass Spectrometry. Issue 3 (1st February 2016) - Mi, Si; Lim, David W.; Turner, Justine M.; Wales, Paul W.; Curtis, Jonathan M.
Abstract: An LC/MS/MS‐based method was developed for the determination of individual bile acids (BA) and their conjugates in porcine bile samples. The C18‐based solid‐phase extraction (SPE) procedure was optimized so that all 19 target BA and their glycine and taurine conjugates were collected with high recoveries for standards (89.1–100.2 %). Following this, all 19 compounds were separated and quantified in a single 12 min chromatographic run. The method was validated in terms of linearity, sensitivity, accuracy, precision, and recovery. An LOD in the low ppb range with measured precisions in the range of 0.5–9.3 % was achieved. The recoveries for all of the 19 analytes in bile samples were all >80 %. The validated method was successfully applied to the profiling of BA and their conjugates in the bile from piglets treated with exogenous glucagon‐like peptide‐2 (GLP‐2) in a preclinical model of neonatal parenteral nutrition‐associated liver disease (PNALD). The method developed is rapid and could be easily implemented for routine analysis of BA and their conjugates in other biofluids or tissues.